The effect of bicuspid aortic valve versus tricuspid aortic valve as a risk factor for aortic dilatation: a systematic review and meta-analysis - Rianda, Rama Azalix; Danindra, Ivan; Wartono, Dicky Aligheri (Journal of Indonesia Vascular Access, 2025)
Background: The enlargement of the ascending aorta (AA) is a frequent finding in clinical practice. Age, gender, and body size have been shown to be important determinants of AA diameter. One of the most prevalent congenital heart conditions is bicuspid aortic valve (BAV) disease, which primarily affects male subjects and has a population prevalence of 0.5% to 2.0%. Purely severely stenotic BAVs developed a moderate dilation of the aorta at an early age, while TAVs (Tricuspid Aortic Valves) did not. This study aims to compare BAV and TAV as risk factors for aortic dilatation. Methods: A systematic literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines by using PubMed/Medline, Scopus, and ScienceDirect databases according to PICO. The studies obtained were adjusted to the eligibility criteria. We conducted a journal appraisal assessment using the CASP 2024 tools for the 10 included studies. Meta-analysis was performed using Review Manager 5.4. Result: Out of 208 studies, 10 studies are included for a systematic review according to eligibility criteria. From the baseline characteristics, BAV with aortic dilatation is often seen at a younger age compared to TAV. 5 studies are analyzed for the incidence risk of aortic dilatation between BAV and TAV group (OR 5.16; 95% CI 2.69, 9.92; p<0.001) and 6 studies are analyzed for the aortic diameter between BAV and TAV group (OR 0.55; 95% CI -1.37, 2.46; p<0.58). Conclusion: Our systematic review-meta-analysis study found that there is an increase in ithe ncidence risk of aortic dilatation in BAV patients compared to TAV patients. Our study result supports the guideline designed by the American Association for Thoracic Surgery that suggests patients undergoing concurrent heart surgery, concomitant ascending aorta/root repair should be actively performed when the aortic diameter is 45 mm.